The Indonesian Values Scale: An Empirical Assessment of the Short-Form Scale - Sihombing, Sabrina O. (UI Scholars Hub, 2014)
Culture is an important variable that influences people’s behavior. Culture involves several elements, such as language, myth, ritual, custom, artifact, law, and values. However, values are known as the most important elements in describing culture. In 2011, a survey was conducted in Jakarta, Bandung, Semarang, and Surabaya with 2,000 respondents to identify current Indonesian values. The results showed that Indonesian values could be operationalized with 35 items and seven dimensions of mutual assistance: democracy, religion, harmony, hospitality, religious fanaticism, and individualism. On the other hand, the extensive number of Indonesian values items (i.e., 35 items) may have several practical problems, such as longer questionnaires and sample requirements. Therefore, a short-form scale of Indonesian values is needed to enhance the understanding of Indonesian culture through its values. This research aimed to provide a short-form instrument for understanding Indonesian values. Specifically, this research explores psychometric assessments, including the dimensionality, reliability, and validity of the original and short-form scales of Indonesian values. In 2013, a survey with more than 1,000 questionnaires was distributed in Jakarta, Tangerang, Bandung, Semarang, and Surabaya. This research produced a short-form scale of Indonesian values that involves 13 items and the three dimensions of religion, democracy, and harmony. This paper provides an analysis of the data, a discussion of the findings, research limitations, and directions for future research.